1997
DOI: 10.1021/es9604018
|View full text |Cite
|
Sign up to set email alerts
|

Iron Redox Cycling in Surface Waters:  Effects of Humic Substances and Light

Abstract: The purpose of this study is to examine the mechanism of photo-oxidation of natural dissolved organic matter (DOM) in the presence of iron. This process is of interest in natural waters for several reasons:  as a significant sink of DOM in sunlit surface waters; as a source and sink of reactive oxygen species (HO2/O2 •-, hydrogen peroxide, and HO•) and as a factor controlling iron speciation. Studies were conducted in laboratory model systems containing fulvic acid and lepidocrocite (γ-FeOOH) particles at pH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
323
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(335 citation statements)
references
References 100 publications
9
323
0
1
Order By: Relevance
“…The mechanism proposed for the oxidation of Fe II in seawater by King et al (1995) has been widely accepted for studies of iron speciation and redox cycling in natural systems (Emmenegger et al, 1998;King, 1998;King and Farlow, 2000;Rose and Waite, 2002;Voelker et al, 1997).…”
Section: Redox Cycling Of Iron In Seawatermentioning
confidence: 99%
“…The mechanism proposed for the oxidation of Fe II in seawater by King et al (1995) has been widely accepted for studies of iron speciation and redox cycling in natural systems (Emmenegger et al, 1998;King, 1998;King and Farlow, 2000;Rose and Waite, 2002;Voelker et al, 1997).…”
Section: Redox Cycling Of Iron In Seawatermentioning
confidence: 99%
“…Therefore, in irradiated systems, the enhanced Fe(II) production in nanorods can also be a result of the (021) surface planes with higher density of surface O-H groups. Recent field and laboratory studies have shown that, in marine surface waters and in acidic surface waters, light-induced reduction of Fe(III) to Fe(II) is a key process and serves to increase the solubility of marine aerosol Fe (22,23). As such, any processes that enhance production of soluble Fe(II) are important and increase total iron dissolution.…”
mentioning
confidence: 99%
“…This leads to an increased • OH-radicai production [15,45]. The experiments [46,47] to Fenton/Photo-Fenton reactions. Fig.…”
Section: Basic Considerations On Photo-fenton Mediated Reactions Actimentioning
confidence: 97%